Pandangan Orientalis Terhadap Ketokohan Nabi Muhammad Saw: Analis Terhadap Pemikiran Annemarie Schimmel(W. 2003 M) - Batu Bara, Mhd. Alfarizi (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
According to Annemarie Schimmel, there is a uniqueness in the sirah of the Prophet Muhammad that made Annemarie Schimmel analyze the various uniqueness of the figure of the Prophet Muhammad in her view as an orientalist. In this research, we will discuss the attitude or views of the orientalists towards the figure of the Prophet Muhammad. In particular, it will be explained how the views, admiration and analysis of Annemarie Schimmel (W. 2003 AD) towards the Prophet Muhammad SAW. which is different from the views of other orientalists who consider Islam a religion that is not true, radical, the source of lies of Muhammad and others. This study aims to analyze Annemaria Schimmel's views on the character of the Prophet Muhammad. different from other orientalist figures. This research is an analytical research study of the views of figures through literature review (Library Research). This research is a descriptive analysis in nature and its study is how the results of the analysis of Annemarie Schimmel's views on the character of the Prophet Muhammad saw. Data collection techniques were obtained from the analysis of Annemarie Schimmel's views which were sourced in her essay entitled And Muhammad Is His Messenger: The Veneration Of The Prophet In Islamic Piety (And Muhammad Is the Messenger of Allah) and her other books and journals related to analysis of Annemarie Schimmel's thoughts and sirah of the Prophet Muhammad SAW. From the results of Annemarie Schimmel's analysis that the Prophet Muhammad as a unique figure, this uniqueness is contained in the sirah of the Prophet. Then the results include the Prophet Muhammad, the Prophet Muhammad as the intercessor in the final yaumil as rahmatan lil'alamin, as the leader of the ummah, the Qur'an and the event of the isra' mi'raj as the miracle of the Prophet, and the Prophet Muhammad as an example of tasawwuf.